Occurrence of overt seizures in comatose survivor patients treated with targeted temperature. Issue 11 (18th October 2017) - Eilam, Anda; Samogalskyi, Volodymyr; Bregman, Gennady; Eliner‐Avishai, Sarit; Gilad, Ronit
Abstract: Background: Unconscious patients after out‐of‐hospital cardiac arrest have a high risk of death. Therapeutic hypothermia is recommended by international resuscitation guidelines in order to attenuate secondary destructive physiological processes such as reperfusion injury, apoptosis, and cerebral edema. The target temperature to reach ranges between 32 and 34°C for at least 24 hr. Hypothermia can induce metabolic disturbances. There are some reports in the literature indicating the presence of seizures during targeted temperature management. On the other hand, postanoxic seizures are a sign of unfavorable neurological outcome. The purpose of this study was to evaluate the occurrence of overt seizures in comatose survivor patients treated with targeted temperature in respect to overt seizures in a normal temperature group of comatose patients. Methods: This was a retrospective study of unconscious adults post cardiopulmonary resuscitation, hospitalized in the intensive care unit during the years 2008–2015. The patients were divided into two groups: those treated with hypothermia and those with normal body temperature. Both groups were evaluated for the appearance of overt seizures during their hospitalization which was the primary outcome of the study. Results: The data of 88 consecutive unconscious patients after out‐of‐hospital cardiac arrest were collected. Twenty‐six patients were treated with targeted temperature (32–34°C) and 62 patients with normal temperature. In the hypothermic group, 6 (23%) patients developed overt seizures during hospitalization compared to 11 (17%) in the normothermic group. The mortality rate was similar in both groups, 16 (61%) in the hypothermic group and 38 (61%) in the conservative group. According to the present study, overt seizures were more common in the group treated with hypothermia. Abstract : We retrospectively investigated the occurrence of seizures in comatose patients after cardiopulmonary resuscitation. We compared overt seizures in the group treated with targeted temperature versus the normothermic one. The hypothermic group had an increased amount of overt seizures.